Factors Affecting Recurrent Lateral Ankle Sprain in Athletes - Pooja Sharma1 , Shaurya Dayal2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Lateral ankle sprains are one of the most common sports injuries that an athlete may endureduring their career. If not treated correctly, it often leads to recurrent twisting of the ankle joint, causingdisruption of the ligaments in the ankle joint. Various anthropometric factors such as height, weight, BMI, aswell as previous ankle sprain history are assessed as potential predictors of recurrent lateral ankle sprain. Thepotential factors are correlated with the Foot and Ankle Ability Measure- Sports Sub Scale to assess theircontribution to a recurrent lateral ankle sprain in athletes. The FAAM Sport subscale is used to determinethe functioning of the ankle joint, as recorded by the subjects themselves.Methodology: The questionnaire is sent to the candidates who fall under the inclusion criteria, and they areasked to fill the questionnaire. The participants were between the age of 18-30 years. Both male, as well asfemale athletes were included in the study. Each athlete must have played at least 3 competitive sports in thelast 1 year, and they must have a history of at least 1 lateral ankle sprain. The collected data is then compiledand analyzed.Result: After the analysis of the data, previous ankle sprain history depicted maximum correlation withthe FAAM- Sport Subscale, as well as an inverse relationship, with a reading of -2.89, and significance of0.27. Height depicted an inverse relationship as well, with -.119 when compared to FAAM Sport Sub-scale.Weight also shows an inverse relationship (-0.053) when correlated with the FAAM Sport sub-scale. BMIdoes not show any correlation with the FAAM Sport Subscale (+0.002).Conclusion: Previous ankle sprain history, height and weight depict an inverse relationship with the FAAMSport Subscale, indicating that, as their score increases, the functioning of the ankle joint decreases, andhence becoming a potential factor for recurrent ankle sprains. BMI however, does not depict any correlationwith the FAAM sport sub-scale.